Fifa World Cup Qatar 2022: análise do megaevento como estratégia de mudança da imagem do destino turístico - Lima, Geisa Caroline Santana (Universidade Federal de São Carlos, 2025)
The practice of producing images of tourist destinations, in the context of mega sporting events, with the aim of increasing the international prestige of nation-states, has been recurrent since 1934, the year in which Italy, under the management of Benito Mussolini, hosted the FIFA World Cup. The political instrumentalization of major sporting events has been, since 2010, investigated under the name “sportswashing”, with the purpose of identifying and analyzing the tools used in attempts to “wash” a country’s reputation, through the mobilization of sporting appeal - via the holding of mega sporting events - and sponsorship or investment in major football clubs. Actions characterized as “sportswashing” are intended to create a façade image that, for example, in the case of Eastern countries, allows them to be promoted as a modern, liberal and Western friendly country (Martínez, 2018 apud Soyland, 2020, p. 57). The FIFA World Cup Qatar 2022 constitutes a recent experience of this practice and, with the prospect of contributing to the set of studies aimed at evaluating the perception of tourists in relation to the image of tourist destinations (Kaplanidou et al., 2016; Evers; Pineda, 2023), this research will seek to analyze the way in which Brazilian tourists perceive Qatar's tourist image, verifying the impacts and effectiveness of the country's image cleaning strategy, through the holding of a mega sporting event - FIFA World Cup Qatar 2022 - in the image perceived by these tourists. For this purpose, the image of Qatar was analyzed based on the General Model of Images in Tourism (Santana Talavera; Pinto, J. 2008 apud Pinto, R., 2012, p.567), in order to understand how the country's images were formed, following each of the seven stages of the model, and the interference they have on each other. This is an interdisciplinary research with a qualitative approach, of an exploratory and descriptive nature, with collection and analysis of primary and secondary data using bibliographical, documentary and interview research techniques, which will be carried out with a sample of approximately 0.5 % of Brazilians who participated in the mega sporting event in Qatar, in 2022. The question guide for conducting the interviews will consider, above all, the contributions of the Semiological Model, developed by MacCannel (1976 apud Pinto, 2012, p.554) and the Model Three-dimensional, presented by Echtner and Ritchie (1993 apud Pinto, 2012, p.562). The analyzes of the data collected in the interviews were carried out using the content analysis technique (Bardin, 1977). The results obtained from the research show that hosting mega-sporting events in countries with a negative or resistant image for tourism, as is the case with the country analyzed, allows tourists to visit a place they never imagined they would be, due to factors such as fear. This experience can lead, depending on their personal experiences, to more positive perceptions of the location, due to the meaning attached to the competition and the tangible and intangible changes it brings to the country.
Fifa World Cup Qatar 2022: analysis of the mega-event as a strategy for changing tourist destination image
Keywords: Imagens de Destinos Turísticos; Turismo; Megaeventos Esportivos; FIFA World Cup Qatar 2022; Sportswashing; CIENCIAS SOCIAIS APLICADAS::TURISMO